2019
DOI: 10.5937/ekopolj1903771p
|View full text |Cite
|
Sign up to set email alerts
|

The consumption of organic foods by the student population in the Republic of Serbia

Abstract: The beginning of the 21st century has noted a change in the attitude of modern man towards health and the pursuit of a healthy lifestyle. Thus, particular emphasis is placed on the importance of a healthy diet and a healthy lifestyle. The importance of nourishing nutrition and health-related issues has been recognized and raised on the state level. Thus, numerous national campaigns promote healthy nutrition aimed at improving the overall health of the nation. Health in general, as well as healthy eating habits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The results of studies conducted in Malaysia showed that only 2.3% of respondents buy organic food using online shopping websites while the remaining 97.7% purchase organic food products from supermarkets, convenience stores, or other sources (Hasanov & Khalid, 2015). In the research that was conducted in Serbia in previous years (Stojić & Dimitrijević, 2020;Palić et al, 2019;Končar, 2019;Kranjac, Vapa-Tankosić & Knežević, 2017;Vlahović & Šojić, 2016), during the analysis of the sales channels through which consumers most often buy organic food, online shopping was not even examined. This indicates that this type of organic food purchase remains underdeveloped in Serbia.…”
Section: Introductionmentioning
confidence: 99%
“…The results of studies conducted in Malaysia showed that only 2.3% of respondents buy organic food using online shopping websites while the remaining 97.7% purchase organic food products from supermarkets, convenience stores, or other sources (Hasanov & Khalid, 2015). In the research that was conducted in Serbia in previous years (Stojić & Dimitrijević, 2020;Palić et al, 2019;Končar, 2019;Kranjac, Vapa-Tankosić & Knežević, 2017;Vlahović & Šojić, 2016), during the analysis of the sales channels through which consumers most often buy organic food, online shopping was not even examined. This indicates that this type of organic food purchase remains underdeveloped in Serbia.…”
Section: Introductionmentioning
confidence: 99%